The interaction between ginseng and gut microbiota - Zhao, Linxian; Sui, Mingxiu; Zhang, Tongbo; Zhang, Kai (Frontiers in Nutrition, 2023)
The importance of the gut microbiota to human health is attracting increasing attention. It is also involved in ginseng metabolism, mediating the bioactive metabolites of ginsenosides. In response, ginseng, known as the king of herbs, can regulate intestinal flora, including promoting probiotics and restricting the growth of harmful bacteria. Specifically, the interactions between ginseng or ginsenosides and gastrointestinal microbiota are complex. In this review, we summarized the effects of ginseng and ginsenosides on the composition of gut microbiota and discussed the gut microbiota-mediated biotransformation of ginsenosides. In particular, their therapeutic potential and clinical application in related diseases were also summarized.